Advance directives in action in a regional palliative care service: "road testing" the provisions of the Medical Treatment Act 1988 (VIC) - Brown, Margaret; Fisher, John W; Brumley, David J; Ashby, Michael A; Milliken, Jan (Journal of law and medicine, 2005)
In order to explore the usefulness and acceptability of the provisions of the Medical Treatment Act 1988 (Vic) for palliative care patients in a rural region in Victoria, Australia, between July and December 2004 patients were given information explaining the Act and the opportunity to discuss it with the research officer. Grounded theory methodology was used to evaluate client responses. Findings suggested that palliative care patients are willing to engage in advance care planning but they have to be well enough and need skilled, practical, face-to-face assistance to complete the required legal forms. Written materials alone are not adequate, but provide the opportunity for medical staff to have conversations about death and dying. Doctors and nurses should understand the provisions of the Act to assist patients and families. It is recommended that advance care planning, appropriate to the jurisdiction, be an integral part of the palliative care assessment process.